2012
DOI: 10.3354/dao02440
|View full text |Cite
|
Sign up to set email alerts
|

First report of Perkinsus beihaiensis in Crassostrea madrasensis from the Indian subcontinent

Abstract: Protozoan parasites of the genus Perkinsus are considered important pathogens responsible for mass mortalities in many wild and farmed bivalve populations. The present study was initiated to screen populations of the Indian edible oyster Crassostrea madrasensis, a promising candidate for aquaculture along the Indian coasts, for the presence of Perkinsus spp. The study reports the presence of P. beihaiensis for the first time in C. madrasensis populations from the Indian subcontinent and south Asia. Samples col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
(37 reference statements)
0
17
0
1
Order By: Relevance
“…Similar symptoms were observed in C. rhizophorae (SABRY et al, 2009) and C. gasar (QUEIROGA et al, 2015) from Brazil. In contrast, Sanil et al (2012) reported some digestive tubule lesions in Crassostrea madrasensis, but these lesions were not directly associated with P. beihaiensis.…”
Section: Discussionmentioning
confidence: 74%
“…Similar symptoms were observed in C. rhizophorae (SABRY et al, 2009) and C. gasar (QUEIROGA et al, 2015) from Brazil. In contrast, Sanil et al (2012) reported some digestive tubule lesions in Crassostrea madrasensis, but these lesions were not directly associated with P. beihaiensis.…”
Section: Discussionmentioning
confidence: 74%
“…Sequencing demonstrated that this was P. beihaiensis, with 98 to 100% similarity with the sequences available at NCBI, as deposited by Sanil et al (2012) and Sabry et al (2013), to India and the Northeast Brazil, respectively. The obtained sequence was deposited in GenBank with number KX923545.…”
Section: Resultsmentioning
confidence: 99%
“…The preferred location of P. beihaiensis in the digestive epithelium has been reported in previous studies on the genus Crassostrea (Moss et al, 2008;Sanil et al, 2012;Sabry et al, 2013;Queiroga et al, 2015;Luz and Boehs, 2016). Oysters with severe infection (level 4, Ray's scale) showed disorganization of gastric and intestinal epithelia and were assessed as impaired by the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently the species contributes to about 4000 tonnes to the fast growing bivalve farming sector in India. The rapidly expanding edible oyster farming and its management points to the importance of information on the parasites/pathogens of this species which is presently very limited (Samuel, 1978;Bijukumar, 2001;Sanil et al, 2012;Suja et al, 2014).…”
Section: Introductionmentioning
confidence: 99%